Kebangkitan Ekonomi Islam Dalam Ubah Suai Di Pasar Global - Wening Purbatin Palupi Soenjoto (ACTIVA: Jurnal Ekonomi Syariah, 2018)
Abstract The global market is a wide door for producers to carry out trade transactions for goods and services. Competition emerged very rapidly and producers applied marketing strategies to get greater profits. Capitalist and socialist economies still continue to dominate the world economy. From the dominance of the two systems and supported by easy-to-find global economic conditions and competition, also the development of material-oriented societies, has an impact on the lack of attention and willingness to understand and implement other economic systems that are more just, human-oriented and built on faith, namely the Islamic economy. Especially in the current era of globalization which is the best means for all Muslims as an effort to introduce Islamic culture and teachings throughout the world. With the existence of the global market, there will be no more binding matters. In fact, the related and national boundaries seem to be lost in the economic field, especially trade. The global market has made very rapid fluctuations in economic development and the rise of Islamic economics must become a sustainable shaping axis and benefit in a symbiotic way of mutualism for all parties involved in the economy. Keywords: Islamic economics, capitalist economy, global market, globalization, world economy.